(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Unexplained infertility is a diagnosis of exclusion after systematic evaluation fails to identify a cause. Oligospermia is defined traditionally by a sperm density <20 million/ml. Intrauterine insemination has been used to treat infertile couples for almost 200 years. Intrauterine insemination is specially appropriate for cases with mild male factor infertility, anovulation, endometriosis with at least one patent tube and unexplained infertility. IUI is considered as a first line procedure due to its simplicity, easy management low cost. In IUI (intra uterine insemination) processed semen is inserted in the uterine cavity using a small catheter at the time of ovulation in stimulated cycle. Objective: To evaluate the pregnancy rate per cycle of IUI in unexplained infertility and mild male factor infertility. Materials and methods: This study was interventional study carried out in the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka in collaboration with Labaid Fertility Centre, Labaid Specialized Hospital, Dhaka from July 2016 to June 2018. Married couples with female partner aged 18-35 years, male partner 20-50 years. Total 148 subjects were included in this study. The patients were divided to groups groups. In group A 74 patients were unexplained infertility and group B 74 patients were mild form of oligoastheno-teratozospermia. Data was collected using a structured questionnaire (research instrument) containing all the variables of interest. The questionnaire will be finalized following pretesting. Data was processed and analyzed with the help of computer program SPSS (Statistical package for Social Science) with version 25. Results: This study shows in female the average age was 29.16 years in unexplained infertility group (Group A) and 27.55 years in mild form of oligoasthenoteratozospermia group (Group B). The average age was 36.63 years in unexplained infertility group (Group A) and 35.18 years in mild form of oligoasthenoteratozospermia group (Group B). Semen concentration was 94.27 m/mil in unexplained infertility group and 16.37 m/mil in mild form of oligoastheno-teratozospermia group. 6.75% of pregnancy in unexplained infertility and 4.05% of pregnancy in mild form of oligoasthenoteratozospermia. It was observed that prewash concentration was 89.01 m/mil, prewash motility was 68.78, prewash morphology was 58.82, postwash concentration was 59.80 m/mil and post was motility was 99.21 in unexplained infertility. On the other hand in mild form of oligoasthenoteratozospermia prewash concentration was 17.76 m/mil, prewash motility was 31.35, prewash morphology was 15.00, postwash concentration was 20.33 m/mil and post was motility was 84.86. The difference was statistically significant (<0.05). Conclusion: Intra Uterine Insemination (IUI) is a cheap and minimally invasive method compared to other methods of assisted reproduction. The IUI procedure is simple and may be performed even if the woman is not receiving medication to improve her egg production. Many physicians will encourage women to take medications to stimulate the ovaries in order to increase egg production and, hopefully, the chance of achieving pregnancy. J Dhaka National Med. Coll. Hos. 2023; 29 (02): 13-18